GCG Sebagai Pilar Enterprise Risk Management: Studi Kasus PT. Martine Berto Tbk 2021-2023 - Lusiana Mufidah; Elok Fauzia; Retno Wulandari; Yasmin Kamila; Putri Intan Nur Rizkiyah; Achmad Afandi; M. Cholilur Rochman (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The beauty and personal care industry in Indonesia has been growing rapidly with increasingly tough competition, so companies need to manage risks optimally. PT Martina Berto Tbk has recorded consistent net sales growth during the 2021–2023 period, but its net profit growth hasn’t shown the same stability. This study aims to analyze how the implementation of Good Corporate Governance (GCG) can support the implementation of Enterprise Risk Management (ERM). The method used in this study is a descriptive qualitative approach with a case study, conducted through an analysis of the 2021–2023 Annual Reports and Sustainability Reports. The results show that the GCG structure consistently supports the process of identifying, evaluating, mitigating, and monitoring risks, thereby increasing the effectiveness of ERM implementation.